Factors influence the acceptance of smart farming technologies (SFTs) among youth in higher learning education in Malaysia. - Majid, Nurul Aziemah; Mohamed Haris, Nur Bahiah; Arif Shah, Jasmin (UMK Press, 2025)
Smart farming, a modern approach that integrates technology and innovation into agricultural practices, presents a compelling opportunity to attract young people to the agricultural sector. This approach has the potential to transform youth perceptions of agriculture, shifting it from a perceived outdated and unappealing career path to a viable and profitable option. Therefore, this research aims to determine the factors influencing the acceptability of Smart Farming Technologies (SFTs) among youth in selected public universities. The data were collected using a simple random sampling technique. The respondents involved in this study were undergraduate agriculture students (from second year and above) who studied at the UPM, UMK, UMT, UMS, and UiTM (Jasin). A total of 395 respondents were employed from the total population 2963 using the Raosoft Calculator. Data collection was conducted through Google Forms and has been analysed using SPSS version 27. Findings indicate that all factors exhibited strong positive correlations (>0.6) with the adoption of SFTs among youth. Attitude emerged as the most influential factor, followed by knowledge and awareness, demonstrating the highest standardized coefficient (0.406) and t-value (7.034). These results suggest that a positive attitude towards SFTs is a critical factor in influencing their acceptance among young people. This study emphasizes the crucial role of knowledge, attitude, and awareness in both promoting SFTs among youth and empowering them to facilitate the adoption of agricultural technology.